Revitalization of Islamic Character Values in Local Folklore and its Implication on Character Education - Umar, Mardan; S., Waway Qodratulloh; Ma'arif, Muhammad Anas; Ismail, Feiby; Rahman, Rini (Universitas Islam Negeri Mataram, 2025)
This study aims to identify the Islamic character education values in the local folklore of Si Kabayan Saba Kota and explore the challenges and solutions of local folklore as a tool for character education in the era of globalization, as well as its implications for character education. The study employs a descriptive qualitative approach, analyzing the content of scenes, dialogues, and narratives in the film. Additional data were obtained through interviews with Sundanese cultural experts and educators, as well as a literature review on local wisdom and character education. The findings reveal that folklore encompasses various relevant character values, including religiosity, honesty, responsibility, social care, courage, simplicity, and a love for culture. This folklore highlights the significance of local wisdom and Islamic character values as a powerful educational medium for shaping the character of the young generation in the era of globalization. Islamic character education based on local cultural values through folklore can be implemented by instilling moral knowledge, moral feelings, and moral actions.